Say More and Be More Coherent: How Text Elaboration and Cohesion Can Increase Writing Quality - Scott A. Crossley; Danielle S. McNamara (Journal of Writing Research, 2016)
This study examines links between essay quality and text elaboration and text cohesion. For this study, 35 students wrote two essays (on two different prompts) and for each, were given 15 minutes to elaborate on their original text. An expert in discourse comprehension then modified the original and elaborated essays to increase cohesion, resulting in a 2 (prompt) x 2 (original content, elaborated content) x 2 (original cohesion, improved cohesion) design. Expert raters scored the essays for overall quality and text coherence. In terms of overall essay quality, increasing text content (i.e., elaboration) and improving cohesion both led to significant gains in expert judgments of writing quality, and a combination of both elaboration and improved cohesion led to increased scores over increased cohesion alone. Judgments of text coherence were increased by improved cohesion (but not elaboration); and a combination of both elaboration and improved cohesion led to higher human ratings of coherence in comparison to the original and elaborated versions. The results have important implications for writing theories, writing success, writing pedagogy, and standardized testing.